Socioeconomic Determinants of Healthy Ageing and the Contextual Effect of Peer Group: A Multilevel Evidence from Blora, Central Java - Niena Ayu Cahyaningtyas; Aris Sudiyanto; RB. Soemanto (Journal of Epidemiology and Public Health, 2019)
Background: Healthy ageing is about "optimizing opportunities for good health, so that older people can take an active part in society and enjoy an independent and high quality of life". This study aimed to examine the socioeconomic determinants of healthy ageing and the contextual effect of peer group in Blora, Central Java.Subjects and Method: This was a cross-sectional study conducted in Blora, Central Java.A sample of 200 elderly was selected for this study by snowball sampling. The dependent variable was healthy ageing. The independent variables were nutrition intake, age, religiosity, education, and perceived financial position. Data on healthy ageing was collected by WHOQOL-BREF. The other variables were measured by questionnaire. The data were analyzed by a multilevel model.Results: Healthy ageing was positively affected by strong religous belief (b= 6.75; 95% CI= 3.91 to 9.59; p<0.001), better education (b= 8.16; 95% CI= 4.26 to 12.07; p<0.001), better perceived financial position (b= 6.46; 95% CI= 2.86 to 10.07; p<0.001), and good nutritional status (b= 6.79; 95% CI= 3.76 to 9.83; p<0.001).Conclusion: Healthy ageing is positively affected by strong religous belief, better education, better perceived financial position, and good nutritional status.Keywords: healthy ageing, religious belief, elderly, ageing, peer support groupCorrespondence: